TRADITIONS AND INNOVATIONS IN TEACHING ENGLISH IN MUTUAL COMPARISON - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2023)
The article evaluates traditional and innovative methods of teaching English. In the modern and rapidly developing world, it is necessary to select stable pedagogical methods that allow not only to educate students, but also to reveal and improve skills to form the student's competence. The traditional teaching method, despite its stability and many years of experience, is already giving way to innovative methods: the use of computer technology and foreign experience in teaching a foreign language.